The Influence of Salesperson Competence and Sales Programs on Toyota's Sales Performance Moderated by The Leadership at Pt. Astra International, Tbk. – Tso - harman, Harman; Napitupulu, Elfrida (International Journal Labs, 2024)
This study aims to analyze the influence of sales force competence and sales programs on Toyota sales performance, with leadership as a moderating variable at PT. Astra International Tbk. - Toyota Sales Operation (TSO). The research method used is Partial Least Square (PLS) to analyze data collected through questionnaires from sales force, sales force leaders, and sales program sections at PT. Astra International Tbk. - TSO. The results of the study indicate that Sales Force Competence has a positive and insignificant influence on Sales Performance. Sales programs have a positive and significant influence on sales performance. In addition, the interaction between sales force and leadership does not have a significant influence on sales performance and its influence tends to be negative with a very low moderation effect. And the interaction between sales programs and leadership has a positive and significant influence on sales performance, although the moderation effect remains low. This study is expected to provide practical implications for companies in improving sales performance through the development of sales force competence, optimization of sales programs, and the application of the right leadership style.